Bacillus subtilis DSM29784 Alleviates Negative Effects on Growth Performance in Broilers by Improving the Intestinal Health Under Necrotic Enteritis Challenge - Wang, Yuanyuan; Xu, Yibin; Xu, Shengliang; Yang, Jinyong; Wang, Kaiying; Zhan, Xiuan (Frontiers in Microbiology, 2021)
Along with banning antibiotics, necrotic enteritis (NE), especially subclinical enteritis (SNE), pose a significant threat to the chicken industry; however, probiotics are a potentially promising intervention. We aimed to investigate the beneficial effects of Bacillus subtilis DSM29784 (BS) on the treatment of Clostridium perfringens (CP)-induced SNE in broilers. A total of 360 1-day-old broiler chicks were divided into three treatment groups namely control (Ctr), SNE, and BS treatments groups (BST), all of which were fed a basal died for 21 days, and then from day 22 onwards, only the BST group had a BS supplemented diet (1×109 colony-forming units BS/kg). On day 15, all chicks, except the Ctr group, were challenged with a 20-fold dose coccidiosis vaccine and 1 ml CP (2 × 108) on days 18 to 21 for SNE induction. Beneficial effects were observed on growth performance in BST, compared to SNE broilers. BST treatment alleviated intestinal lesions and increased the villus height/crypt depth ratio. Further, BST broilers showed increased maltase activity in the duodenum compared with SNE chicks, and a significantly decreased Caspase-3 protein expression in the jejunum mucosa. Moreover, an increased abundance of Ruminococcaceae and Bifidobacterium beneficial gut bacteria, and an altered gut metabolome were observed. Taken together, we demonstrate that manipulation of microbial gut composition using probiotics may be a promising prevention strategy for SNE by improving the composition and metabolism of the intestinal microbiota, intestinal structure, and reducing inflammation and apoptosis.